Theories of self-care and self-management of long-term conditions by community-dwelling older adults: A systematic review and meta-ethnography. (October 2021) - Lawless, Michael T.; Tieu, Matthew; Feo, Rebecca; Kitson, Alison L.
Abstract: Rationale: The proportion of older adults living with long-term conditions (LTCs) is increasing. Self-care and self-management approaches are seen as valuable in helping older people with LTCs to manage their health and care, yet the theoretical overlaps and divergences are not always clear. Objectives: The objectives of this review were to: (1) systematically identify and appraise studies of self-care or self-management of LTCs by community-dwelling older adults (aged ≥60 years) either informed by, applying, creating, or testing theory; (2) explore similarities or points of convergence between the identified theories; and (3) use a meta-ethnographic approach to synthesise the theories and group related concepts into core constructs. Methods: We conducted a systematic theory synthesis, searching six electronic databases. Three reviewers independently screened titles and abstracts followed by full texts and two reviewers appraised study quality. Theoretical data were synthesised within and across individual theories using meta-ethnographic line-of-argument synthesis. Results: A total of 141 articles (138 studies) and 76 theories were included in the review. Seven core constructs were developed: (1) temporal and spatial context; (2) stressors; (3) personal resources; (4) informal social resources; (5) formal social resources; (6) behavioural adaptations; and (7) quality of life outcomes. A line of argument was developed that conceptualised older adults' self-care and self-management as a dynamic process of behavioural adaptation, enabled by personal resources and informal and formal social resources, aimed at alleviating the impacts of stressors and maintaining quality of life. Conclusion: This synthesis provides an overview of theories used in research on older adults' LTC self-care and self-management. Our synthesis describes the complex interplay of intrinsic and extrinsic factors influencing self-care and self-management behaviours and provides considerations for future research, intervention design, and implementation. The utility of the constructs in research and practice requires further attention and empirical validation. Highlights: Self-care and self-management are valuable in managing long-term conditions. Older adults often face additional challenges in addressing their care needs. We conducted a synthesis of theories of self-care and self-management. We developed seven core theoretical constructs for further exploration. Strategies targeting multiple societal levels and key actors are needed.